Search 75,605 tutors
FIND TUTORS
Ask a question
1 0

3 (x-4)+7=-3+x-24

Tutors, please sign in to answer this question.

2 Answers

X = -11

3 (x-4)+7=-3+x-24

-Add (-3+-24=-27)-

3 (x-4) +7 = x-27 

-Move -27 to other side and add it to 7 (27+7 = 34)

3 (x-4) + 34 = x

-Distribute 3- 

3x-12+34=x

(34-12 = 22)

3x+22=x

-Subtract x from both sides-

2x+22=0

-Move 22 to other side

2x=-22

-Divide by 2 to get X alone

x=-11

Combine like terms on each side, then distribute the 3, then move terms algebraically to get all the x's on one side of the =, and all the constants on the other side.

Then combine like terms and solve.

Combine: 3(x - 4) + 7 = x - 27

Distribute: 3x -12 + 7 = x - 27

Combine: 3x - 5 = x - 27

Subtract x from each side: 2x - 5 = -27   Add 5 to each side: 2x = -22

Solve: 2x = -22, Divide by 2 each side: x = -11